Angle-selective optical filter for highly sensitive reflection photoplethysmogram - Hwang, Chan-Sol (Biomed Opt Express, 2017)
We report an angle-selective optical filter (ASOF) for highly sensitive reflection photoplethysmography (PPG) sensors. The ASOF features slanted aluminum (Al) micromirror arrays embedded in transparent polymer resin, which effectively block scattered light under human tissue. The device microfabrication was done by using geometry-guided resist reflow of polymer micropatterns, polydimethylsiloxane replica molding, and oblique angle deposition of thin Al film. The angular transmittance through the ASOF is precisely controlled by the angle of micromirrors. For the mirror angle of 30 degrees, the ASOF accepts an incident light between - 90 to + 50 degrees and the maximum transmittance at - 55 degrees. The ASOF exhibits the substantial reduction of both the in-band noise of PPG signals over a factor of two and the low-frequency noise by three times. Consequently, this filter allows distinguishing the diastolic peak that allows miscellaneous parameters with diverse vascular information. This optical filter provides a new opportunity for highly sensitive PPG monitoring or miscellaneous optical tomography.